2017
DOI: 10.1037/stl0000095
|View full text |Cite
|
Sign up to set email alerts
|

Which forms of active learning are most effective: Cooperative learning, writing-to-learn, multimedia instruction, or some combination?

Abstract: Despite support for active learning, little research has directly compared active techniques to determine which are most beneficial for student learning and motivation. The current study compared the active-learning techniques of cooperative learning (CL) and writing-to-learn (WTL) while also varying the modality of presentation (textual or multimedia) of lessons on key concepts and classic experiments in child development. Undergraduates (N = 165) in 4 sections of a developmental psychology course completed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The results showed that the majority of the research used was experimental with a quasiexperimental type by comparing it with other methods or conventional methods. Several other methods used as comparisons include the expository learning method, active learning, and problem-based learning (Sawyer et al, 2017). The results show that when compared to other methods, cooperative learning has several advantages in improving learning outcomes and learning activities in chemistry subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the majority of the research used was experimental with a quasiexperimental type by comparing it with other methods or conventional methods. Several other methods used as comparisons include the expository learning method, active learning, and problem-based learning (Sawyer et al, 2017). The results show that when compared to other methods, cooperative learning has several advantages in improving learning outcomes and learning activities in chemistry subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of iterative assignments that begin early, start simply, build on one another and focus on the synthesis and summary of ideas and include peer review produces deep learning of content via communication of diverse and complex ideas (Balgopal et al., 2018). Building on low‐stakes activities stimulates student engagement and builds self‐efficacy (Camfield et al., 2020; Sawyer et al., 2017). Additionally, the knowledge that their work potentially reaches large and diverse audiences drives student's engagement and motivation (Konieczny, 2016).…”
Section: Taking the Plungementioning
confidence: 99%
“…Writing is one of the primary media used in Wikipedia assignments and is consistently associated with increased student engagement (Camfield and Land, 2017). In particular, the use of iterative assignments that begin early, start simply, build on one another and focus on the synthesis and summary of ideas and include peer review can create deep learning of content via communication of diverse and complex ideas (Balgopal et al, 2018), Building on low-stakes activities stimulates student engagement and builds self-efficacy (Sawyer et al, 2017;Camfield et al, 2020). Additionally, the knowledge that their work potentially reaches large and diverse audiences drives student's engagement and motivation (Konieczny, 2016).…”
Section: Wikipedia Assignmentsmentioning
confidence: 99%